CIRCUITI COMMERCIALI E NON COMMERCIALI DEL SAPERE - VITIELLO, NATO Defense College, Roma, Giuseppe (BIBLIOPOLIS, 2020)
This is the first of a three article series devoted to the scholarly communication commercial and non-commercial chains. Innovation in both sectors does not follow the same dynamics. The critical dimension of economic change in the publishing sector is innovation in products, when it relates to content, and innovation in processes. As things stand, only when scholarly communication industries innovate in processes, will they acquire a longlasting competitive advantage over their competitors. Other factors of innovation in the scholarly publishing industry are collective action and, more importantly, institutional policies. The non-commercial scholarly communication sector, mainly libraries, evolves according to a different dynamic: State and local governmental policies to begin with, and cooperative undertakings.